The Effect Of Modified Domino Cards Game On Students’ Vocabulary Mastery - suhaili, Muhamad; S, K. Dedy Sandiarsa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This research aimed to find out the effect of modified domino cards game on students’ vocabulary mastery at the seventh grade students of Mts Negeri 3 Mataram in academic year 2019/2020. The research was pre experimental design. The population of the study was the seventh grade students that consisted of five classes. The sample of the study was class VII C that consists of 39 students. The class was treated using modified domino cards game. The result of the study shows that there is significance positive effect of modified domino cards game on students’ vocabulary mastery. The data of the research were gathered from data analysis and inferential analysis. In data analysis, the mean score of pre test was 44.62 and post test was 73; the mode score of pre-test was 45.9 and post test was 78.3; the median score of pre-test was 44.8 and post test was 78.14; the score of standard deviation on both of the test was 11.27. In inferential analysis, the result showed that the value of t-test (18.94) was higher than the value of t-table (2.024) with significance level of 5%. The finding of this study led into the conclusion that the use of modified domino cards game shows positive effect on students’ vocabulary mastery at the seventh grade of Mts Negeri 3 Mataram. This is based on the t-test > t-table (18.944 > 2.024) in degree significant of 5%. It means that Ha was accepted and Ho was rejected. Therefore, it can be concluded that modified domino cards game gives positive effect on students’ vocabulary mastery at the seventh grade students of MTs Negeri 3 Mataram in academic year 2019/2020